A CONSTRUCTING ATTITUDE MEASUREMENT TOWARD ENVIRONMENTAL LITERACY: VALIDITY TESTING - Iyan Irdiyansyah; Burhanuddin Tola; Awaluddin Tjalla (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2020)
The objective of this study was to test the attitude measurement construction toward students’ environmental literacy. It was modified from Lingqiong Wu, 2013 who was constructed in China. It was adapted and modified in Indonesian version based on Indonesian culture. As much as three dimensions of environmental literacy, they are cognitive, skill, and attitude/behavior toward the environment. Stratified random sampling was used to choose as much as 250 primary school students in Bogor West Java. Confirmatory Factor Analysis (CFA) by using M-Plus was used to analyze the data. Based on the finding showed that the Chi-square was 465.976* with the degree of freedom (df) = 78. The p-value of this result study was 0.0000, and Root Mean Square Error of Approximation (RMSEA) = 0.141, Comparative Fit Index (CFI) = 0.938. It was concluded based on the result above that the model was fit with the data.